Agro-Ecological Zoning by GIS: A Case Study of the Bafra and Carsamba Plains in Turkey - KARA, TEKIN; GULER, MUSTAFA (Asian Journal of Chemistry, 2010)
This study introduce a pilot agro-ecological zoning exercise for areas of the Carsamba and Bafra plains near Samsun, Turkey, using geographical information systems (GIS). The various information layers such as soil, topography and climate dataset and models were used to determine agroecological zones. Weighted factor analyses were used to evaluate and analyze the data layers and the resulting maps were produced for the two plains. The results obtained are presented as a thematic map for practical use.